Efektifitas Penggunaan Otak Kanan dan Otak Kiri terhadap Pencapaian Hasil Belajar Mahasiswa - Baiq Yuni Wahyuningsih; M. Abdurrahman Sunni (PALAPA, 2020)
This study aims to see an overview of the use of the right and left brain of STMIK Mataram students and how much it affects the achievement of their learning outcomes. This type of research is a descriptive study with a quantitative approach. Data collection was carried out through questionnaires and test questions. The data analysis technique was carried out by using descriptive statistics and simple regression analysis to determine the closeness of the correlation coefficient between the independent variable (X), namely the level of use of the right brain and left brain and the dependent variable (Y), namely student learning outcomes. The results showed that in general, the level of use of the students' right brain was moderate with a percentage of 34.375%. The number of students who think using the right brain in the very high category is 6.25%, the high category is 31.25%, the low and very low category is 25% and 3.125%. The level of use of the students' left brain is classified as moderate with a percentage of 56.25%. Students who think using the left brain are in the very high category of 9.375%, the high category is 15.625%, the low and very low category is 12.5% ​​and 6.25%. Meanwhile, for the achievement of learning outcomes in general, the learning outcomes score was classified into the low category with a value range of 53 - 65 as many as 12 people (37.5%), 8 people (25%) and very high respectively. 4 people (12.5%). While the determinant coefficient obtained was 31.7%. In other words, that the use of the right brain and left brain has an effect of 31.7% on the calculus learning outcomes achieved by students.